2019
DOI: 10.4103/jfmpc.jfmpc_750_19
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam versus phenytoin in children with status epilepticus

Abstract: Background:To compare the efficacy and safety of intravenous levetiracetam and phenytoin in status epilepticus.Methodology:A prospective, randomized controlled, nonblinded study was conducted in children 1 month to 12 years of age with active seizure and with status epilepticus. A total of 104 children were randomly allocated to either group 1 (levetiracetam) or group 2 (phenytoin) on the basis of computer-generated random number table. Children already on antiepileptic drugs, very sick children with shock, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…All patients had established SE. Consistent with previous findings of Wani et al, which was a smaller study, this study showed no significant differences in fosphenytoin, levetiracetam, and valproate efficacies across the age groups [ 19 ]. Also, there was no remarkable difference between fosphenytoin and levetiracetam efficacies in the study subjects [ 20 ].…”
Section: Reviewsupporting
confidence: 92%
See 4 more Smart Citations
“…All patients had established SE. Consistent with previous findings of Wani et al, which was a smaller study, this study showed no significant differences in fosphenytoin, levetiracetam, and valproate efficacies across the age groups [ 19 ]. Also, there was no remarkable difference between fosphenytoin and levetiracetam efficacies in the study subjects [ 20 ].…”
Section: Reviewsupporting
confidence: 92%
“…In a recent study, Chamberlain et [19]. Also, there was no remarkable difference between fosphenytoin and levetiracetam efficacies in the study subjects [20].…”
Section: Table 1: Comparison Of Efficacies Of Levetiracetam and Phenytoin In Se Patientsmentioning
confidence: 83%
See 3 more Smart Citations